The cradle of heaven-human induction idealism: agricultural intensification, environmental consequences and social responses in Han China and Three-Kingdoms Korea. Issue 4 (7th August 2016) - Zhuang, Yijie; Lee, Heejin; Kidder, Tristram R.
ABSTRACT: Han China (206bc –ad 220) witnessed significant population growth, pronounced technological development, intensified agricultural practices and the construction of large-scale hydraulic engineering projects in the Yellow River. These processes coincided with increased frequency and intensity of major floods along the Yellow River. The interactions between flooding and social-technical developments fundamentally reshaped the politics of the Han and stimulated the formation of so-called heaven-human induction idealism. This Confucian environmental ethic gradually became a powerful orthodoxy that shaped political and economic behaviours and society's perspective on and actions towards utilizing environmental resources and transforming landscapes. Similar processes played out in Three-Kingdoms Korea (ad 300–668). The Korean case exemplifies how, as in China, this idealism was a product of the long-term interplay between state formation and the environment through the development of intensive agriculture.